Analysis Of Financial Health Level On Financial Performance In Cement Companies Listed On The Indonesian Stock Exchange (Idx) - Dhea Zatira; Ria Puspitasari (Fakultas Bisnis, 2020)
This study aims to analyze the Level of Financial Soundness on Financial Performance in Cement Companies that are Go Public Listed on the Indonesia Stock Exchange (BEI). Analysis of the level of financial health using the Altman Z-Score with several ratios, namely the ratio of Working Capital to Total Assets (X1), the ratio of retained earnings to total assets (X2), the ratio of EBIT to Total Assets (X3), the ratio of stock market value to book value ofabilities (X4), the ratio of Sales to Total Assets (X5) to the dependent variable on Financial Performance (Return on Assets). The data analysis technique used in this research is the Altman Z-Score with the criteria for bankruptcy and to find its effect with the panel data regression model assisted by E-Views software. The results of the calculation and analysis of the Z-Score criteria in cement companies in Indonesia, it is known that there is no cement company whose company finances are stated in a healthy condition. One company is prone to bankruptcy (gray zone) while the rest according to the Z-Score criteria are bankrupt. Furthermore, based on the panel data regression examiner simultaneously the five independent variables on financial performance (Y), while partially the working capital ratio to total assets (X1) affects financial performance (Y), the retained earnings ratio to total assets (X2) has no effect on Financial performance (Y), EBIT ratio to total assets (X3) affects financial performance (Y), stock market value ratio to book value of liabilities (X4) has no effect on financial performance (Y), Sales to Total Assets ratio (X5) affect financial performance.